Numeralia dalam Bahasa Melayu Jambi di Kecamatan Tanah Sepenggal Lintas Kabupaten Bungo Provinsi Jambi - Rizki Dewi Astuti; Siti Ainim Liusti (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
The objective of this study's implementation is to describe the numeralia in Jambi Malay used in the Tanah Sepenggal Lintas District, Bungo Regency, in Jambi Province. This research type falls under qualitative research utilizing descriptive methodologies. The information collected in the context of this study, it takes the form of a set of words in Malay that contain numerals. Two approaches are employed in this investigation: the auditory and verbal interaction methods. The technique employed to validate the data or information in this studi is the triangulation method. The findings of this research are first, derived from the basis of numeralia in Jambi Malay in Tanah Sepenggal Lintas District, two are found, namely (1) the basic numeral form consisting of two forms totaling 19 data, (2) the derived numeral form consisting of three forms of a total of 100 data. Second, based on the types of numerals in Jambi Malay, two types of numerals were found in Tanah Sepenggal District, Bungo Kabuoaten, Jambi Province, namely (1) types of definite numerals consisting of three types totaling 99 data. (2) types of non-definitive numerals found in a total of 21 data.